2007
DOI: 10.1002/app.25559
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of terpolymer of N‐cyclohexylmaleimide, methyl methacrylate, and acrylonitrile

Abstract: Terpolymers of N-cyclohexylmaleimide, methyl methacrylate, and acrylonitrile (AN) at different AN feed content were synthesized by suspension polymerization. The thermal properties of the terpolymers such as glass transition temperature (T g ) and Vicat softening temperature (T Vicat ) were determined by torsion braid analysis and Vicat softening temperature tester, respectively. The value of T g and T Vicat decreased with increasing AN feed content. Thermogravimetric analyses were carried out with the results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Yang and Sun (7) reported terpolymers of N-cyclohexylmaleimide, methyl methacrylate and acrylonitrile by suspension polymerization. Michael et al (8) prepared terpolymer of 8-hydroxyquinoline, guanidine and formaldehyde and also studied thermal degradation to ascertain its thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…Yang and Sun (7) reported terpolymers of N-cyclohexylmaleimide, methyl methacrylate and acrylonitrile by suspension polymerization. Michael et al (8) prepared terpolymer of 8-hydroxyquinoline, guanidine and formaldehyde and also studied thermal degradation to ascertain its thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…Metal-polymer complexes namely metalcomposites have many applications such as in waste water treatment for metal recovery, in hard water treatment via metal-ion exchange, protective coatings, thermally stable and reinforced materials, manufacturing of antimicrobial and surgical materials, gels and ointments for medical uses and other biological activity [3], [4]. According to the literature protocols, it has been found that different typed polymers used as ligand to formed variety of metal-polymer materials [5], [6], [7]. The chemical properties of nitrogen containing functional groups such as azo group, thiazole group and cyanide and thiocyanate groups have been intensively researched in various fields and especially in polymers areas for achieved required and high quality materials [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, copolymerization of methyl methacrylate (MMA) with maleimide (MI) which has a five‐member ring was discussed by Kita et al . The copolymers have not only high T g , but also excellent toughness . Whereas the residue of MI monomer makes the light transmittance of copolymers decrease sharply .…”
Section: Introductionmentioning
confidence: 99%